我的老師們 - 陳, 思和 (City University of Hong Kong Press, 2025)
Great teachers do more than teach; they inspire and guide, leaving an indelible mark on students’ lives. This memoir recounts how the author, while studying and working at Fudan University, received guidance and support from leading writers, scholars, and educators—including Jia Zhifang, Ba Jin, Chen Zizhan, Shi Zhecun, and Wang Yao. With delicate, emotive prose, the author shares little-known anecdotes and moments with each mentor, recounting their instruction and support. These stories not only reveal strong bonds but also reflect the spirit of modern Chinese intellectuals—their rigorous scholarship and noble character, remaining open, unafraid, and steadfast in the face of oppression and upheaval—worthy of emulation by teachers and students alike.